Strategi manajemen inovatif di bank syariah: analisis implementasi dan dampak terhadap keberlanjutan lembaga keuangan Islam di Indonesia - Aspasya, Marsha Aura (Maliki Interdisciplinary Journal, 2025)
The development of the Islamic financial industry in Indonesia demands management innovation that can address the challenges of competition and digitalization. This study aims to analyze the implementation of innovative management strategies in Islamic banks and their impact on the sustainability of Islamic financial institutions. The approach used is a descriptive qualitative method through a literature review of five journals from the UIN Malang Repository for the 2021–2024 period. The analysis shows that the implementation of innovations in the areas of service digitalization, strengthening human resources based on Islamic values, and developing Islamic financial products contribute significantly to efficiency and customer trust. Furthermore, the integration of technologies such as artificial intelligence (AI) and Islamic fintech can expand the reach of services without compromising the principles of maqasid sharia. In conclusion, management innovation aligned with Islamic values is a crucial element in maintaining the sustainability and competitiveness of Islamic financial institutions in the modern era.